The religious orders and the pastoral task in the works of Juan Bernal Díaz de Luco (1495-1556) (History Journal «Jerónimo Zurita», 2024)
Juan Bernal Díaz de Luco (1495-1556) is an important figure when it comes to considering the ways of thinking about the reform of the Church and the government of souls in the Spain of Charles V. His works focused strongly on these two topics, dealing mainly with the role of bishops and priests, their forms of behavior and their pastoral task. However, Díaz de Luco also dedicated some texts and passages to the place of religious orders in the context of the care of souls. In this sense, this article will address two aspects. On the one hand, the elaboration of texts for the call to the members of the religious orders to abandon conventual life and embark on the conversion of the American peoples. On the other hand, the task that Díaz de Luco assigned to monks and friars in writings that were fundamentally intended for the secular clergy. In such manner, the paper shows some ways in which collaboration and conflict between the different sectors of the clergy in the sixteenth century were thought.
Keywords: Religious Orders; Pastoral Task; Reform of the Church; Juan Bernal Díaz de Luco; Sixteenth Century